Pengaruh Kualitas Produk Dan Desain Produk Terhadap Kepuasan Pelanggan Pengguna Sepeda Motor Honda Supra X 125 Fi - Mulyana, Mumuh; Setiawan, Budi; W, Denny Haryono (LPPM Institut Bisnis dan Informatika Kesatuan, 2016)
To satisfy the customers, the companies must gives the deep attention for the products qualities and design. The Product Quality and design factors can be factors for customers to considerate the choosing of product. This situation must be faced by PT Astra Honda Motor as the motorcycles manufacture in Indonesia. The purposes of this study are to find out the effect of product quality on Motorcycles Honda Supra X125 Fi’s customer satisfaction, to know the influence of product design to customer satisfaction and to know the influence of the product quality and products design to customer satisfaction. The results of this study are (1) the regression equation: Y = 1.202 + 0.891 X1 + 0.203 X2. It means that all the independent variables has a positive effect on customer satisfaction. (2) 74,1% variablity of customer satisfaction was explained by product quality and product design (adjusted R square = 0.861). (3) The Product quality have the significant positive effect to customer satisfaction, (4) Product Design have the significant positive effect to customer satisfaction, (5) In simultan regression, product design and product quality have the significant influence on customer satisfaction.